Formulating policy activities to promote healthy and sustainable diets. Issue 13 (18th August 2015) - Lawrence, Mark A; Friel, Sharon; Wingrove, Kate; James, Sarah W; Candy, Seona
Abstract: Objective: To develop a policy formulation tool for strategically informing food and nutrition policy activities to promote healthy and sustainable diets (HSD). Design: A policy formulation tool consisting of two complementary components was developed. First, a conceptual framework of the environment–public health nutrition relationship was constructed to characterise and conceptualise the food system problem. Second, an 'Orders of Food Systems Change' schema drawing on systems dynamics thinking was developed to identify, assess and propose policy options to redesign food systems. Setting: Food and nutrition policy activities to promote HSD have been politicised, fragmented and lacking a coherent conceptual and strategic focus to tackle complex food system challenges. Results: The tool's conceptual framework component comprises three integrated dimensions: (i) a structure built around the environment and public health nutrition relationship that is mediated via the food system; (ii) internal mechanisms that operate through system dynamics; and (iii) external interactions that frame its nature and a scope within ecological parameters. The accompanying schema is structured around three orders of change distinguished by contrasting ideological perspectives on the type and extent of change needed to 'solve' the HSD problem. Conclusions: The conceptual framework's systems analysis of the environment–public health nutrition relationship sets out the food system challenges for HSD. The schema helps account for political realities in policy making and is a key link to operationalise the framework's concepts to actions aimed at redesigning food systems. In combination they provide a policy formulation tool to strategically inform policy activities to redesign food systems and promote HSD.